Processing System and Evaluation Microbiological Quality of Drinking Water Fountain in Surabaya City - Dian Novitasari (Universitas Airlangga, 2020)
Introduction: Drinking water fountain (KASM) is one of the innovations of the Regional Drinking Water Company (PDAM) Surya Sembada Surabaya City to provide drinking where the location is in various public facilities. Health problems in people who consume KASM water can occur when the quality of water is not eligible. Unsafe drinking water can interfere with health and can cause waterborne disease. The purpose of writing this article is to identify the processing system and analyze the quality of water microbiology of KASM. Method: This type of research was a descriptive observational with case design report. Subject of study was drinking water fountain (KASM) was one of the innovations of the Regional Drinking Water Company (PDAM) Surya Sembadin the city of Surabaya. The data used was secondary data on 13 samples of KASM locations originating from the PDAM Surya Sembada Surabaya City and various literature. The method of data analysis used is qualitative. Result and Discussion: Water treatment in each KASM unit is an advanced process of water treatment plant (IPAM) PDAM Surya Sembada City of Surabaya. A series of water treatment processes through several equipments, consisting of: pressure tank, basin, low and high pressure switch, booster pump, radar, tank container, UV lamp, RO, Flow Reject, remineral, hexagonal, post-carbon, 1 micron catridge, GAC, 5 micron Catridge, and solenoid. Results of the evaluation of the microbiological quality of KASM based on the data quality Report water in January 2019-January 2020 indicates that the total parameters coliform at 13 point location 4.69% are not eligible, while for the parameter fecal coliform 100% qualified drinking water quality. Conclusion: monitoring of water quality, processing system, and sanitation need to be applied regularly to provide safe drinking water for the community